PAPER -Gun Firing of Innovative no highlt _May 31 2023 SN6168 PA LOG #409-22.pdf - Gill, Philip (Cranfield University, 2023)
25MM GUN DEMONSTRATION OF NITROGEN –DOPED BORON PROPELLANTS Thelma Manning - US Army DEVCOM Armaments Center 9th International Nitrocellulose Symposium - Paper
Keywords: 'nitrocellulose'